2022
DOI: 10.1088/2050-6120/ac7037
|View full text |Cite
|
Sign up to set email alerts
|

Determination of amoxicillin trihydrate impurities 4-hydroxyphenylglycine (4-HPG) and 6-Aminopenicylanic acid (6-APA) by means of ultraviolet spectroscopy

Abstract: Amoxicillin is one of the broad-spectrum β-lactam antibiotics widely used in the treatment of many diseases. It is inevitable that 4-hydroxyphenylglycine (4-HPG) and 6-Aminopenicylanic acid (6-APA), which are used during the production of this antibiotic, are incorporated into the molecular lattice of the product as impurities. Today, many expensive methods and chemical devices are used for the purification of Amoxicillin by determining 6-APA and 4-HPG, which are defined as impurities. In this study, it was ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The synthesis of xanthenes, especially thioxanthenes, has increased remarkably in recent years due to their wide range of biological and pharmacological properties. As an example of its biological and pharmacological properties, anticancer, antitumor, antiviral, antimicrobial, antibacterial, and anti-inflammatory activities can be cited. Moreover, some types are also used as materials in dye technology, , sensor, , and organic light-emitting diodes (OLEDs) due to the conjugation and heteroring in their structures, ensuring optical and electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of xanthenes, especially thioxanthenes, has increased remarkably in recent years due to their wide range of biological and pharmacological properties. As an example of its biological and pharmacological properties, anticancer, antitumor, antiviral, antimicrobial, antibacterial, and anti-inflammatory activities can be cited. Moreover, some types are also used as materials in dye technology, , sensor, , and organic light-emitting diodes (OLEDs) due to the conjugation and heteroring in their structures, ensuring optical and electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The literature predominantly focuses on the adverse impact of introducing impurities structurally similar to the primary molecule on crystal growth. The separation of AMCT from its own degradation products, in particular, has garnered emphasis. In their investigation, Feng et al demonstrated that an increase in the concentration of degradation products leads to a decrease in AMCT nucleation . In another study, Ghassempur et al detailed the integration of impurities into the AMCT crystal lattice and its consequent impact on the process.…”
Section: Introductionmentioning
confidence: 99%